ANALISIS HUBUNGAN ANTARA INFLASI DAN PERTUMBUHAN EKONOMI: KASUS INDONESIA - Ismail Fahmi Lubis (Quantitative Economics Journal, 2014)
The Phenomena and trends of level of inflation which seem to be high as caused by factors or government policies whilst the level of economic growth averagely shows high and sustainable growth drawing the unusual macroeconomic condition in Indonesia. This research is conducted to find Correlation and Short-run as well as Long-run relationship between inflation and economic in Indonesia during 1968-2012. Besides, it is to find Granger-Causality between the Consumer Price Index (CPI) and Gross Domestic Product (GDP). It first tests its Unit-Root by Augmented Dickey Fuller and Dickey Fuller test, then it tests its Cointegration by Johansen Cointegration test and its causal relationship by Granger-Causality test as well as it makes mechanism of Error Correction Model (ECM). It is found both inflation and economic growth have no Unit-Root. It is found both inflation and economic growth have Correlation. It is found significantly long-run relationship through the probability value of its residual and short-run relationship through the probability value of inflation and economic growth in its differentiation. It is then found significantly one-way Granger-causality GDP causes CPI but not found one-way Granger-causality CPI causes GDP.